Implementation of Compensation in State-Owned Enterprises in Samarinda City (Case Study of DAMRI General Company) - Dwi Oktaviany Kommala; Thalita Rifda Khaerani (Dinasti Publisher, 2024)
Companies must enhance the welfare of their employees to ensure they feel safe and comfortable in their work environments, thereby enabling them to contribute maximally. One effective method for improving employee welfare is through compensation. The objective of this study is to examine the implementation of compensation in State-Owned Enterprises located in Samarinda City. This research employs a qualitative approach. The findings indicate that compensation has a positive and significant effect on the work productivity of employees at Perum DAMRI. Furthermore, an increase in work motivation contributes to heightened job satisfaction among employees. The incentives provided by the company motivate employees to perform optimally in pursuit of organizational goals. Both direct and indirect compensation positively influence job satisfaction. Direct compensation includes periodic salaries, while indirect compensation encompasses benefits such as insurance, health coverage, and pension severance pay. Perum DAMRI in Samarinda offers equitable compensation without discrimination between office and field workers, taking into account factors such as length of service and performance.